An Interesting Six-Connected 3D Nanowater Framework Constructed from Turbine-Type (H2O)18 Clusters Based on a Mn(III) Complex - Li, Chun-Hong; Huang, Kun-Lin; Dou, Jian-Min; Chi, Ying-Nan; Xu, Yan-Qing; Shen, Long; Wang, Da-Qi; Hu, Chang-Wen (Crystal growth & design, 2008)
A rare six-connected 3D nanowater framework constructed from turbine-type (H2O)18 clusters has been observed in a Mn(III) Schiff base complex [Mn(vanen)(Cl)(H2O)]·2H2O (1, H2vanen = N,N′-bis(3-methoxysalicylidene)-1,2-diaminoethane). And each (H2O)18 cluster includes a chair configuration cyclic hexamer and six dangling dimer water units. The nanochannels of three-dimensional hydrogen-bonded water network are filled by the dimer of [Mn(vanen)(Cl)(H2O)]2 molecules. Interestingly, the crystal stacking of metal complexes composed of [Mn(vanen)(Cl)(H2O)]12 shows a head-to-head turbinelike motif. Moreover, compound 1 displays strong photoluminescence in the solid state at room temperature.